Writing Knowledge, Forging Histories: Metallurgical Recipes, Artisan-Authors and Institutional Cultures in Early Modern London. (27th May 2021) - Kilburn-Toppin, Jasmine
ABSTRACT: This article explores a succession of goldsmiths' recipe books or books of secrets, which emerged from the early modern Royal Mint and Goldsmiths' Company. It argues that in their rich descriptions of metallurgical workshop practices, techniques and tools, these artisan-authors also narrated contested institutional histories and their own life experiences. For London's assayers (who had responsibility to test the precious metal content of bullion, plate and coin), authorship functioned as a status-enhancing activity. Writing treatises was a means of articulating expertise and of rooting that skilled identity beyond the self, within a much longer trajectory of institutional production and regulation.